2016
DOI: 10.1155/2016/4567146
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Conventional Collagen Sponge and Collagen-Gelatin Sponge in Wound Healing

Abstract: The objective of this study was to compare the effectiveness of the collagen-gelatin sponge (CGS) with that of the collagen sponge (CS) in dermis-like tissue regeneration. CGS, which achieves the sustained release of basic fibroblast growth factor (bFGF), is a promising material in wound healing. In the present study, we evaluated and compared CGSs and conventional CSs. We prepared 8 mm full-thickness skin defects on the backs of rats. Either CGSs or CSs were impregnated with normal saline solution (NSS) or 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Gelatin is a partial hydrolysis product of native collagen and characterized by non-toxicity, non-carcinogenicity, biocompatibility, and biodegradability 1 3 ; gelatin is widely used in the pharmaceutical and medical fields, such as in wound dressing materials 4 , 5 , tissue engineering scaffolds 6 8 , and drug delivery carriers 9 , 10 . Gelatin can be prepared in a spongy form to be suitable for tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin is a partial hydrolysis product of native collagen and characterized by non-toxicity, non-carcinogenicity, biocompatibility, and biodegradability 1 3 ; gelatin is widely used in the pharmaceutical and medical fields, such as in wound dressing materials 4 , 5 , tissue engineering scaffolds 6 8 , and drug delivery carriers 9 , 10 . Gelatin can be prepared in a spongy form to be suitable for tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A previous study observed new bone formation in the maxillary sinus using only gelatin sponges as the gra material, which may provide adequate bone mass for implant placement. 7 Since gelatin sponges have excellent biocompatibility, degradation into physiological endproducts [8][9][10] and suitable interaction with cells and other macromolecules, [11][12][13][14] they have received increasing attention as scaffolds in the emerging eld of tissue engineering. [15][16][17] Bone morphogenetic proteins (BMPs) are potent growth factors for bone formation and remodeling, due to their powerful osteoinductive ability.…”
Section: Introductionmentioning
confidence: 99%
“…Newly formed capillaries stained with visible lumen with erythrocytes on anti-CD31 stained sections were evaluated. The number and area of the stained capillaries in 3 squares of 200 μm × 200 μm at the center and both marginal wounds in each section were counted manually 21 . The sum of the capillary numbers or the area in square microns observed in the three squares in each section was used for evaluation.…”
Section: The Histological Evaluation Of Neoepithelialization Granulamentioning
confidence: 99%